PRESERVATION OF UANG ASAP TRADITION IN MELAYU WEDDING: MAQĀSID SHARI'AH PERSPECTIVE - Nofri Andy.N; Siti Humairah (LPPM UNHASY, 2022)
This article is the result of a qualitative field research. This research is a legal sociology research. This article discusses determination of “Uang Asap” in the Malay wedding tradition. The researcher analyzed the research data using the maqasid shariah theory. The location of this research is in Nusapati Village, Sungai Pinyuh District, Mempawah Regency, West Kalimantan. The findings of this study are that in the view of maqasid sharia, the determination of smoked money is included in the category of tahsiniyat (tertiary) benefit. Field data shows that the giving of smoked money is a general tradition, in the sense that it applies to everyone of the Malay ethnicity, especially in Nusapati Village, Sungai Pinyuh District, Mempawah Regency, West Kalimantan. Although the giving of smoked money is not explicitly regulated in maqasid sharia, the giving of smoked money is already a tradition that must be carried out in the community and as long as this does not conflict with aqidah and shari'ah then it is allowed by Islamic law Keywords: “uang asap” tradition, wedding traditions, maqasid shariah theory Daftar Pustaka Abu Ishaq al-Syatibi, Al-Muwafaqat fi Ushul al-Ahkam, Juz ke 2, Kairo: Dar al-Fikr, tt. Abu Malik Kamal bin Sayyid Salim, Sahih Fikih Sunnah, alih bahasa oleh: Khairul Amru Harahap, Faisal Saleh, Ed, Besus Hidayat Amin, Cet II , Jakarta: Pustaka Azzam, 2007. Abu Yasid, Fikih Keluarga, Jakarta: Erlangga, 2005. Abu Ishaq al-Syatibi, al-Muwafaqat fi ushul al-Syari’ah, ( Darul Ma’rifah, Beirut, 1997) Al Amin, Habibi.